A multipath routeless routing protocol with an efficient location update mechanism. (8th June 2011) - Al-Otaibi, Mohammad; Soliman, Hamdy; Zheng, Jun
In this paper, we introduce and evaluate an efficient multipath 'routeless' routing (MRR) protocol. MRR is a form of beaconless geographic routing protocol, and uses a simple location update mechanism to achieve high throughput with few retransmissions. Unlike the standard beaconless routing (BLR) protocol, our main point of comparison, our protocol constructs a single forwarding area to identify nodes between the source and destination. This forwarding area is a rectangular area shape with enough width to allow multiple routes. Promising simulation results show that our protocol outperforms the standard BLR approach with respect to energy consumption, packet delivery ratio, and the average number of hops.